2015
DOI: 10.1007/s10661-015-4732-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in response to bioaccumulation of iron and mercury in Chromolaena odorata (L.) King & Robins.

Abstract: A comparative study was designed to elucidate the effect of iron and mercury on the morphological and anatomical changes as well as bioaccumulation potential in Chromolaena odorata. Plants were grown in half-strength Hoagland nutrient medium artificially contaminated with known quantities of HgCl2 (15 μM) and FeCl3 (1000 μM). Bioaccumulation of Hg and Fe was maximum in the root, and comparatively reduced bioaccumulation was recorded in the stem and leaves. Microscopic studies on morphology and anatomy revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…In our case, the presence of discriminant wavelengths at around 2200 nm could arise from differences between treatments observed toward the end of the experiment, as described above. Many authors have demonstrated that reflectance in the SWIR is particularly dependent on leaf water content and structure, which are affected by water-deficit and by HC and HM contamination. ,,, It might explain the large number of discriminant wavelengths in the SWIR in our study. This is corroborated by the observations in the NIR, which exhibits discriminant wavelengths between 900 and 1100 nm, also consistent with water absorption. , So, despite the intentional elimination of water absorption bands at around 1400 and 1900 nm that are particularly sensitive to the alteration of plant water content, the rest of the SWIR and the NIR were still significant for discriminating the responses of Rubus plants to the different treatments.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In our case, the presence of discriminant wavelengths at around 2200 nm could arise from differences between treatments observed toward the end of the experiment, as described above. Many authors have demonstrated that reflectance in the SWIR is particularly dependent on leaf water content and structure, which are affected by water-deficit and by HC and HM contamination. ,,, It might explain the large number of discriminant wavelengths in the SWIR in our study. This is corroborated by the observations in the NIR, which exhibits discriminant wavelengths between 900 and 1100 nm, also consistent with water absorption. , So, despite the intentional elimination of water absorption bands at around 1400 and 1900 nm that are particularly sensitive to the alteration of plant water content, the rest of the SWIR and the NIR were still significant for discriminating the responses of Rubus plants to the different treatments.…”
Section: Resultsmentioning
confidence: 71%
“…Many authors have demonstrated that reflectance in the SWIR is particularly dependent on leaf water content and structure, 45−47 which are affected by water-deficit and by HC and HM contamination. 24,26,48,49 It might explain the large number of discriminant wavelengths in the SWIR in our study. This is corroborated by the observations in the NIR, which exhibits discriminant wavelengths between 900 and 1100 nm, also consistent with water absorption.…”
Section: Environmental Science and Technologymentioning
confidence: 79%
“…will have an enhanced activity and accumulation. According to Swapna et al, (2015) [29] even in hyper accumulator and hyper tolerant plant species as in other organisms, higher concentrations of toxic chemicals and heavy metals can severely impair central metabolic processes. Belhaj et al…”
Section: Discussionmentioning
confidence: 99%
“…One of the early plant responses to heavy metal stress is the production of ROS in chloroplasts, mitochondria, and peroxisomes and it damages the physiological and biochemical pathways, resulting in decreased cell membrane stability, photosynthesis efficiency, hormonal and nutrient imbalances, inhibition of DNA replication, gene expression and cell division [25,32,33]. According to Swapna., et al [34] even in hyper accumulator and hyper tolerant plant species as in other organisms, higher concentrations of toxic chemicals and heavy metals can severely impair central metabolic processes. So, the study proved that use of sewage sludge as an amendment increased the non-enzymatic anti-oxidant activities in exposed vetiver plants.…”
Section: Bibliographymentioning
confidence: 99%